Sea-level change (Studies in geophysics., 1990)
Explores the views among scientists on the causes and mechanisms of sea-level change. This book examines measurement programs and make recommendations aimed at improving our understanding of the factors that affect sea level. It is meant for scientists, engineers, policymakers, the environmental community, researchers, and students.